KOMPARASI PENERAPAN METODE PEMBELAJARAN CTL DAN OPEN-ENDED DENGAN MEMPERHATIKAN GAYA BELAJAR DITINJAU DARI PRESTASI BELAJAR MATEMATIKA - Dafid Slamet Setiana (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2016)
The purposes of this research are to: (1) describethe achievement in learning mathematics of the students taught using the CTL method and Open -Ended method, (2) compare the achievement in learning mathematics of the students taught using the CTL method and Open-Ended method,(3) compare the effect of student’ mathematics learning styles on their achievement, (4) describe the interaction of teaching methods and the students’ mathematics learning styles on their achievement. This research used a quasi-experimental research design using two experimental groups, they are group of CTL and group of Open-Ended. The instrument using for collect data are test for collect the mathematics achievement data and questionnaire for collect the mathematics learning styles data. The analysis of the data used the multivariate analysis with a two-way analysis of variance with unequal cells, and the post-hoc test involving the Bonferroni procedure. The results of the research are as follows:(1)the achievement in learning mathematics of the students taught usingboth of the CTL and Open-Ended method are well, (2) the achievement in learning mathematics of the students taught using the CTL method are better than Open-Ended, (3) there is an effect of learning style on their achievement, with visual learning styles is better than auditorial learning styles, (4) there is no interaction of teaching method and students’ mathematics learning styles on their achievement in mathematics in the material on opportunities. Keywords: CTL, Open-Ended, learning styles, achievement